1994
DOI: 10.1046/j.1523-1739.1994.08010072.x
|View full text |Cite
|
Sign up to set email alerts
|

Amphibian Declines and Climate Disturbance: The Case of the Golden Toad and the Harlequin Frog

Abstract: Al~tract: The endemic go/den toad (Bufo periglenes) was abundant in Costa Rtca's Monteverde Cloud Forest Preserve in April-May 1987 but afterwards disappeare~ along with local populations of the harlequin frog (Atelopus varius). We examine the possible relationship between these sudden declines and unusually warm, dry conditions in 198Z For our analyses of local weather pattern~ we define a 12-month (July-June) amphibian moisture-temperature cycle consisting of four period~. (1) late wet season; (2) transition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
276
1
13

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 350 publications
(299 citation statements)
references
References 37 publications
9
276
1
13
Order By: Relevance
“…Though 1987 and1988 were the two driest of the 26 yr examined by Lampo et al (2006), these years had the third and fourth highest number of Atelopus collected, a result inconsistent with the hibernaculum hypothesis (it is also worth mentioning that neither chytrid nor population declines were detected in the 1987 dry year). Pounds and Crump (1994) concluded that Atelopus varius actually left their retreat sites en masse during the extreme dry periods of their study.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…Though 1987 and1988 were the two driest of the 26 yr examined by Lampo et al (2006), these years had the third and fourth highest number of Atelopus collected, a result inconsistent with the hibernaculum hypothesis (it is also worth mentioning that neither chytrid nor population declines were detected in the 1987 dry year). Pounds and Crump (1994) concluded that Atelopus varius actually left their retreat sites en masse during the extreme dry periods of their study.…”
mentioning
confidence: 96%
“…One explanation, the climate-linked epidemic hypothesis, has received increased attention in recent years (Pounds and Crump, 1994;Pounds et al, 1999;Kiesecker et al, 2001;Pounds, 2001;Harvell et al, 2002;Ron et al, 2003;Pounds and Puschendorf, 2004;Lampo et al, 2006;Pounds et al, 2006;Santiago-Paredes and La Marca, 2006;Alford et al, 2007;Bosch et al, 2007;Di Rosa et al, 2007;Pounds et al, 2007;Laurance, 2008;Lips et al, 2008). Although it is increasingly clear that various climate anomalies can alter the dynamics of host-pathogen systems (Harvell et al, 2002;Pounds et al, 2007), I suggest caution before accepting the hypothesis that prolonged or intensified dry seasons trigger or exacerbate epidemics of chytridiomycosis, a scenario hypothesized by several authors (Pounds et al, 1999;Ron et al, 2003;Burrowes et al, 2004;Pounds and Puschendorf, 2004;Lampo et al, 2006;Santiago-Paredes and La Marca, 2006), but for which no empirical data exist.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In Central America, the decimation of highland amphibian populations was first noted in Monteverde, Costa Rica (35,36), in the late 1980s, and since then the spread of B. dendrobatidis has been moving in an epidemic wave from the northwest toward the southeast through the cordillera of Isthmian Central America (9,(37)(38)(39)(40). Anticipating the arrival of B. dendrobatidis, an intensive field survey and monitoring program was established in 1998 in the G. D. Omar Torrijos H. National Park (latitude 08.667, longitude −080.592) at 800 m elevation, near El Copé, Panama (9).…”
mentioning
confidence: 99%
“…Some suggested causes for declines include habitat destruction by deforestation and drainage, introduction of predators and competitors, pollution from pesticides, mining and logging, acid precipitation, increased levels of ultraviolet radiation, consumption by humans, introduction of exotic species, and climate change (Elmberg, 1993;Blaustein et al, 1994;Pounds & Crump, 1994). An additional potential factor is mortality on roads.…”
Section: Introductionmentioning
confidence: 99%